National intelligence, basic human needs, and their effect on economic growth - Nik Ahmad Sufian Burhan@Jaohari; Mohd Rosli Mohamad; Yohan Kurniawan; Abdul Halim Sidek (2014)
Self-actualization theory suggests that all individuals hold potential, and they can focus their motivations on actualizing this potential only if all basic and psychological needs are satisfied. Contemporary economic literature has reported that national average intelligence (IQ) is the most robust measure of human capital in raising economic productivity across countries. Treating national IQ as an intrinsic potential of society, our study examined the role of basic and psychological needs (i.e., life expectancy, life satisfaction, and political stability) in moderating the impact of national IQ on economic growth among 118 countries from 1970 to 2010. Hierarchical multiple regression indicates that the independent effects of national IQ, life expectancy, political stability, and life satisfaction on economic growth rate were significantly positive. Furthermore, life satisfaction was significantly negative in moderating the effect of national IQ on growth, while the other two factors were non-significant moderators. Therefore, we suggest that increased life satisfaction reduces desire for better performance, thereby diminishing the effect of IQ on economic growth. This finding is in accordance with the predictions of Maslow's hierarchy of need.